2018
DOI: 10.3389/fpsyt.2018.00155
|View full text |Cite
|
Sign up to set email alerts
|

Profiling of Amino Acids and Their Derivatives Biogenic Amines Before and After Antipsychotic Treatment in First-Episode Psychosis

Abstract: Schizophrenia (SCH) is a heterogeneous disorder, deriving from a potential multitude of etiopathogenetic factors. During the past few years there has been an increasing interest in the role of circulating amino acids (AAs) and biogenic amines (BAs) in the pathophysiology of SCH. In the present study, we aimed to provide an insight into the potential role of alterations in levels of AAs and BAs as well as examine their more specific metabolic shifts in relation to early stage of SCH. We measured 21 AAs and 17 B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
28
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 69 publications
7
28
0
2
Order By: Relevance
“…Previous studies have shown that the use of medication such as antidepressants and levodopa can influence Kyn metabolite concentrations (Myint et al ; Ara and Bano ; Kocki et al ; Gibney et al ; Eskelund et al ; Leppik et al ). Because medication data were not available for all patients, we first conducted sensitivity analyses to assess whether availability of medication use was associated with alterations of Kyn pathway metabolites.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that the use of medication such as antidepressants and levodopa can influence Kyn metabolite concentrations (Myint et al ; Ara and Bano ; Kocki et al ; Gibney et al ; Eskelund et al ; Leppik et al ). Because medication data were not available for all patients, we first conducted sensitivity analyses to assess whether availability of medication use was associated with alterations of Kyn pathway metabolites.…”
Section: Resultsmentioning
confidence: 99%
“…Occurrence of LID is thus unlikely to have had a major influence on our results. Furthermore, clinical and preclinical models have demonstrated that antidepressants and anti‐psychotic drugs, which are commonly used by PD and AD patients, can modulate Kyn pathway activity (Myint et al ; Ara and Bano ; Kocki et al ; Gibney et al ; Eskelund et al ; Leppik et al ). Our results demonstrated that that the use of medication was not involved in the reduced KA content observed in CSF of PD and AD patients.…”
Section: Discussionmentioning
confidence: 99%
“…Acetohydroxyacid synthase, ketol acid reductoisomerase (KARI), dihydroxyacid dehydratase (DHAD), and branched chain amino transferase (BCAT) were the four enzymes operating in L-isoleucine and L-valine biosynthesis (Galili et al, 2016). Abnormal changes in L-isoleucine and L-valine levels have been documented in firstepisode psychosis (Leppik et al, 2018). Our study suggested that abnormal changes in L-isoleucine and L-valine levels are also associated with MMD.…”
Section: Discussionmentioning
confidence: 69%
“…Amino acid levels in patients with various diseases often differ from those of healthy individuals. Alterations in plasma concentrations of amino acids have been reported in liver fibrosis, non-small-cell lung cancer, aortic dissection, first-episode psychosis, and type-2 diabetes mellitus in patients with coronary artery disease (Yang et al, 2013;Leppik et al, 2018). We found that levels of a panel of amino acids (L-alanine, L-isoleucine, L-valine, L-serine, L-threonine, L-methionine, Lphenylalanine, and L-tyrosine) were significantly different in MMD patients relative to HCs.…”
Section: Discussionmentioning
confidence: 99%
“…Аминокислоты и ацилкарнитины как потенциальные метаболомные маркеры Обзоры и лекции ÷åñêîé òåðàïèè. Íàïðîòèâ, ñîäåðaeàíèå òàóðèíà è ñïåðìèíà áûëî îòðèöàòåëüíî àññîöèèðîâàíî ñ ïîâûøåíèåì ÈÌÒ â ïðîöåññå ôàðìàêîòåðàïèè [51]. Òàêèì îáðàçîì, èññëåäîâàíèÿ ðîëè àìèíîêèñëîò â ðàçâèòèè íåaeåëàòåëüíûõ òÿaeåëûõ ïîáî÷íûõ ýôôåêòîâ àíòèïñèõîòè÷åñêîé òåðàïèè ïðàêòè÷åñêè îòñóòñòâóþò, çà èñêëþ÷åíèåì èññëåäîâàíèé ãëóòàìàòà, â îòíîøåíèè êîòîðîãî ÿâëÿåòñÿ äîêàçàííûì ôàêò åãî ó÷àñòèÿ â ìåõàíèçìàõ ðàçâèòèÿ òàðäèâíîé äèñêèíåçèè [52].…”
Section: аминокислоты как маркеры терапевтического ответа на антипсихunclassified